Conjugation of oligonucleotides with activated carbamate reagents prepared by the Ugi reaction for oligonucleotide library synthesis. Issue 6 (26th April 2022) - Kita, Ryosuke; Osawa, Takashi; Obika, Satoshi
Abstract : A solution-phase conjugation method based on the Ugi reaction is reported, which enables the synthesis of an oligonucleotide-tagged peptoid library. Abstract : The DNA-encoded library (DEL) is a powerful tool for drug discovery. As a result, to obtain diverse DELs, many DNA-compatible chemical reactions have been developed over the past decade. Among the most commonly used reactions in medicinal chemistry, multicomponent reactions (MCRs) can lead to the generation of various compounds in a one-step reaction. In particular, the Ugi reaction can easily provide a peptoid library. Thus, we herein report a solution-phase DEL synthesis based on the Ugi reaction. Using 6-(4-nitrophenoxycarbonylamino)hexanoic acid and N -4-nitrophenoxycarbonylglycine as carboxylic acids, peptoids with activated carbamate moieties were obtained as the products of the Ugi reaction. These peptoids were then treated with oligonucleotides bearing a 5′- or 3′-terminal aminohexyl linker to give various oligonucleotide-tagged peptoids in good yields. Moreover, the obtained peptoids could be substituted by a Suzuki cross-coupling reaction and by hydrolysis of the carboxylate ester, followed by condensation with amines. These advances should therefore promote pharmaceutical and medicinal research using DELs.